2007
DOI: 10.1021/jp0795309
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport in Conjugated Aromatic Molecular Junctions:  Molecular Conjugation and Molecule−Electrode Coupling

Abstract: The conductance of a single molecule transport junction is investigated in the Landauer-Imry regime of coherent tunneling transport. Utilizing aromatic systems with thiol end groups, we have calculated using density functional theory the expected conductance of junctions containing molecules with different levels of conjugation and of different lengths. The calculated variations in transport junction conductance are explained in terms of the continuity of the conjugation path between leads. Molecular conjugati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
102
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 129 publications
15
102
0
Order By: Relevance
“…Conjugated aromatic molecules, such as polycyclic hydrocarbons, [1][2][3] and oligomers, such as phenylene-vinylene, 4 represent some of the most frequently investigated molecular wires. Despite the large body of conductivity studies found in the literature, a class of wires with transport properties suitable for molecular circuit usage has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated aromatic molecules, such as polycyclic hydrocarbons, [1][2][3] and oligomers, such as phenylene-vinylene, 4 represent some of the most frequently investigated molecular wires. Despite the large body of conductivity studies found in the literature, a class of wires with transport properties suitable for molecular circuit usage has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Although these SAMs are based on simple oligophenyls and share (we assume) a similar Ph-H//Ga 2 O 3 interface, they differ substantially in their physical and electronic interactions with the metal substrates that form the "bottom" electrodes. Our results indicate that SAMs of SPh n and C≡CPh n on gold, which are characterized by orbital overlap (conjugation) across the molecule, and between the molecule and the electrode, 17 have similar, low values of the attenuation factor β in the simplified Simmons equation 18 (eq. 1) and the injection current, J 0 (β = 0.28 ± 0.03 Å -1 and log|J 0 | = 2.7 ± 0.1 for Au/SPh n ; β = 0.30 ± 0.02 Å -1 and log|J 0 | = 3.0 ± 0.1 for Au/C≡CPh n ).…”
Section: Introductionmentioning
confidence: 86%
“…27,[38][39][40][41][42][43][44][45] These results presented here also agree with theoretical calculations by Ratner and coworkers; these authors predict (using density functional theory, DFT) a value of  = ~0.3 Å -1 for SAMs of polyphenyldithiolates by assuming a continuous conjugation of the molecules with the metal electrodes. 17 We compared the electrical properties of SAMs of SPh n to SAMs of C≡CPh n on Au TS (Figure 2b). Both molecular systems are conjugated; that is, the π-electrons are delocalized across the molecular backbone, but they differ by the chemical structure of the anchoring group (-S-vs. -C≡C-).…”
Section: Introductionmentioning
confidence: 99%
“…Calculations using different formalisms resulted in ␤ = 0.17-0.51 Å −1 . [25][26][27][28][29][30][31][32][33] Kondo et al 27 and Liu et al 31 have studied the influence of the ring torsion angle between the phenyl rings and found ␤ as low as 0.17 and 0.24 Å −1 for planar para-phenylene systems, i.e., no torsion angle between adjacent phenyl rings. The experimentally determined coefficients in large-area molecular junctions match closely to these values.…”
Section: Electrical Characteristics Of Conjugated Self-assembled Monomentioning
confidence: 99%